Review of the current methods in the diagnosis and treatment of scaphoid fractures - Krasin, E (BMJ Group, 2001)
If neglected or misdiagnosed, non-union of a scaphoid fracture will almost inevitably progress to radiographic and symptomatic osteoarthritis of the wrist with subsequent morbidity and lifelong disability, especially in young males in which the fracture is more common. Fractures of the scaphoid bone are the most common fractures of the carpus and second in occurrence among fractures of the wrist. The diagnosis and treatment are not simple. Familiarity with different imaging methods and treatment options is required. The treatment in most cases is conservative and will lead to uneventful union, but an operation may be needed in certain cases primarily and in the treatment of non-union. The current literature on the diagnosis and treatment of scaphoid fractures is reviewed, and the authors try to make a clear and concise picture of this complex and sometimes controversial field.   Keywords: scaphoid; fracture